A novel model predictive control for the three-phase inverter with L type filter in grid-connected mode - Chin, Chee Wai (Nanyang Technological University, 2020)
A model predictive control is proposed in the dq rotating coordinates according to the characteristics of three-phase grid-connected inverters.[1] At each sampling interval, the eight voltage vectors for three-phase connected inverters are evaluated online based on predictive model and the voltage vector that makes the cost function smallest will be applied in the next sampling period, which achieves fast tracking for the given d-axis and q-axis currents. [2]The vector control under grid voltage orientation is used, which realizes the decoupling control for the d-axis current and the q-axis current. The active power and the reactive power are independently controlled by the d-axis current and the q-axis current.[2] Experimental results show that the three-phase connected inverter using model current predictive control has a good static and dynamic performance. Therefore the feasibility and correctness for the control strategy are verified.